Analysis of Immune Responses in Acinetobacter baumannii-Infected Klotho Knockout Mice: A Mouse Model of Acinetobacter baumannii Infection in Aged Hosts - Sato, Yoshinori; Tansho-Nagakawa, Shigeru; Ubagai, Tsuneyuki; Ono, Yasuo (Frontiers in Immunology, 2020)
Acinetobacter baumannii is an important opportunistic pathogen that primarily afflicts elderly people. To clarify the pathogenicity of A. baumannii in the elderly, we investigated immune responses to A. baumannii ATCC 19606 infection in klotho knockout (KO) mice, the mouse model of aging. Following intravenous inoculation, the mice seldom displayed severe symptoms. However, the survival rate was 56% at 7 days post-infection. Bacteria were detected in the lungs of klotho KO mice but not klotho wildtype (WT) mice at 7 days post-infection. Neutrophils, eosinophils, interstitial macrophages, and monocyte/dendritic cell subset in the lungs of klotho KO mice were transiently induced after infection with A. baumannii. The number of alveolar macrophages in klotho KO mice was lower than that in klotho WT mice, except for 1 day post-infection. CD11b expression on neutrophils and alveolar macrophages in the lungs of klotho KO mice was seldom upregulated by the infection. These results suggested that immune functions eliminating bacteria in the lungs of klotho KO mice were insufficient. CD11blow conventional DC cells hardly increased in klotho KO mice infected with A. baumannii. Additionally, the production of interleukin (IL)-10 in the sera of klotho KO mice was significantly higher than that in klotho WT mice, whereas that production of interferon-gamma was not detected in the sera of klotho KO mice. These results suggested that acquired immune responses were hardly induced in klotho KO mice. MCP-1, IL-1β, and MIP-2 expression was higher in the lungs of klotho KO mice infected with A. baumannii than in those of klotho WT mice at 1 day post-infection. These results suggested that pulmonary inflammation was elicited in klotho KO mice during early infection. The expression levels of proinflammatory cytokines significantly correlated with TLR9 expression in the lungs of klotho KO mice. The collective results demonstrate an A. baumannii infection state in aged hosts and suggest that pulmonary inflammation and bacterial burden should be noted in aged hosts even in the absence of severe symptoms of A. baumannii infection.